The Behavioural Biology of Zoo Animals (Taylor & Francis, 2022)
This is the first book on captive animal behaviour, applied to welfare. It enables all aspects of zoo husbandry and management (nutrition, enclosure design, handling & training, enrichment, population management) to be based on a sound knowledge of the species, its evolutionary and natural history.
English
Keywords: Agriculture and farming; Biodiversity; Biology, life sciences; Developmental biology; Ethology and animal behaviour; Fishes as pets and aquaria; Reptiles and amphibians as pets; Veterinary medicine: large animals; Wildlife: general interest; Zoology and animal sciences; Zoology: birds (ornithology); Zoology: fishes (ichthyology); Zoology: invertebrates; Zoology: mammals (mammalogy); zoo biology, Husbandry evidence, Animal welfare, Zoo animal management, Enclosure design, Natural history, Refinement, Zoo research, animal enrichment